Prevalensi dan Pola Kepekaan Acinetobacter baumannii di Ruang Rawat Intensif RS Swasta di Jakarta - Dharmawan, Ade; Devita, Arleen; Gunardi, Wani Devita; Layanto, Nicolas (Jurnal Biomedika dan Kesehatan, 2023)
Background Acinetobacter baumannii is one of the bacteria that cause nosocomial infections, especially in the intensive care unit. These bacteria can cause infections, including bacteremia, pneumonia, urinary tract infections, surgical site infections, and meningitis. Most of these bacteria are multi-resistant to various antibiotics, impacting cure rates and length of stay. This study aimed to determine these bacteria's prevalence and antibiotic susceptibility patterns in the intensive care unit. Methods This research is descriptive research with a retrospective approach. The data was taken from the antibiotic susceptibility report in the intensive care unit of a private hospital in Jakarta in the period January 2020 – December 2021. The antibiotic susceptibility report was processed using the WHONET 2018 software. Results From 681 specimens examined in the intensive care unit, the prevalence of Acinetobacter baumannii was 28.7%, 80% of which came from respiratory specimens. In the sensitivity test results, only the antibiotic Colistin has the best sensitivity to this bacteria, which is 100% sensitive, while other antibiotics have poor sensitivity. Conclusions Acinetobacter baumannii is the bacteria that causes infection in the intensive care unit, with almost all of them being multi-drug resistant bacteria.